TINJAUAN PUSTAKA EVALUASI FARMAKOVIGILANS OBAT ANTIDIABETES ORAL PADA PASIEN RAWAT JALAN DIABETES MELITUS TIPE II - Nena Vauziah Sary (Jurnal Penelitian Farmasi & Herbal, 2022)
Diabetes Mellitus can be treat with pharmacological therapy in the form of oral drug administration. This step has side effects in the form of adverse drug reactions. ADR adapts various factors that can influence the patient to adverse reactions.The purpose of this study was to determine the percentage of incidence of ADR in outpatients with type II diabetes mellitus. This research method is a literature study method searched through PubMed, Google Scholar, and Research Gate using the keywords pharmacovigilance, diabetes mellitus, and adverse drug reaction (ADR). The criteria for articles used were publish in the last 10 years, namely 2012 to 2022, the journal has a title and content that is in accordance with the research objectives. The occurrence of ADR was influence by the gender and type of drug taken. This is in accordance with the research. Oral hypoglycemic drugs that were suspect to be the cause of the onset of ADRs are metformin causing nausea effects and acarbose causing flatulence effects. The use of the Naranjo algorithm is indispensable for assessing the severity of the ADR. Keywords: Farmakovigilans., Diabetes Melitus, ADR